2007
DOI: 10.1007/s11267-007-9148-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Biodegradation of Nonylphenol

Abstract: Abstract. Nonylphenol is the primary breakdown product of nonylphenol ethoxylates (NPEs), a certain class of nonionic surfactants. Nonylphenol has been found to be toxic to aquatic organisms and has been suspected of being harmful to humans due to its xenoestrogenic properties. Although there are known releases of nonylphenol to the environment, there is a lack of data describing the extent of biodegradation. This study thus focuses on much needed information on the biodegradation kinetics of nonylphenol. Oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Other PFCs may be used in cosmetics and hydrophobic coatings, such as used with some clothing items (Inoue et al, 2004). Research has shown these compounds frequently detected in the environment, even being found in deep arctic seas (Rudel et al, 2003;Skutlarek et al, 2006;Farré et al, 2008;Jahan et al, 2008;Arvaniti et al, 2015;Wilkinson et al, 2017). Perfluorinated compounds are not limited to the aquatic environment.…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…Other PFCs may be used in cosmetics and hydrophobic coatings, such as used with some clothing items (Inoue et al, 2004). Research has shown these compounds frequently detected in the environment, even being found in deep arctic seas (Rudel et al, 2003;Skutlarek et al, 2006;Farré et al, 2008;Jahan et al, 2008;Arvaniti et al, 2015;Wilkinson et al, 2017). Perfluorinated compounds are not limited to the aquatic environment.…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…However, its main application is the production of phenolic resin, predominantly as a tackifier in the vulcanization process for the manufacture of rubber tires. Generally, the OP, NP, and their ethoxylates are used in the following: textile industry, production of plastics, water-based paints, herbicides, pharmaceuticals, cosmetics and washing agents, as well as in pulp and paper processing and steel manufacturing (COHIBA 2011a , b ; Jahan et al 2008 ). Such extensive use causes NP and OP as widespread contaminants in natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Different transformation can take place, sometimes producing products that can differ in their environmental behavior and ecotoxicological profile. For example, photodegradation products of some organic pollutants are often more persistent than their corresponding parent compound [12] and exhibit greater toxicity [9,11,13]. Also certain authors [14,15] found that some metabolites are often more concentrated than their parent compounds.…”
Section: Introductionmentioning
confidence: 99%